Bud bank morphology, dynamics, and production in perennial grasses - Ott, Jacqueline Patricia (Kansas State University, 2009)
Perennial grasses on tallgrass prairie primarily reproduce vegetatively via the belowground bud bank, yet the production, dynamics, and morphology of belowground buds is largely unexplored. Since the two main photosynthetic pathway guilds (C3 and C4) on tallgrass prairie vary in their aboveground phenology, their belowground phenology would also be expected to vary. Differences in bud production, development, and spatial arrangement result in different growth forms. Therefore, an extensive biweekly examination of a dominant tallgrass prairie C4 rhizomatous grass Andropogon gerardii and C3 caespitose grass Dichanthelium oligosanthes was conducted over an entire year. Andropogon gerardii and D. oligosanthes have multiple distinctive bud developmental stages. Andropogon gerardii was synchronous in its bud development and its bud bank was composed of multiple annual cohorts. The bud bank of D. oligosanthes was developmentally asynchronous and was comprised of a single bud cohort since its bud bank underwent a complete turnover in early summer. The different roles of buds in the life history of each species reflected their differences in bud longevity, quality, and dormancy. In D. oligosanthes, belowground buds enabled plant survival over the C3 summer dormant period whereas juvenile tillers overwintered during the longer winter dormant period. In contrast, A. gerardii survived its single, winter dormant period as dormant buds. The higher-order bud production observed in D. oligosanthes multiplied its tiller production potential and, along with its shortened internodes, contributed to its caespitose growth form. The rhizomatous growth form of A. gerardii resulted from its lack of higher-order bud production and its elongated internodes. Differences in production of buds per vegetative and flowering tiller were quantified in A. gerardii. Flowering tillers of A. gerardii produced larger numbers of buds per tiller and transitioned a larger proportion of their buds to tillers than did vegetative tillers. Therefore, no tradeoff between sexual and vegetative reproduction was evident. Developmental constraints likely prevented such a tradeoff. Bud bank dynamics offer insight into the control of grass population dynamics, production, and ultimately aboveground net primary production (ANPP) and will be useful in understanding the underlying mechanisms by which management practices and environmental change can alter perennial grasslands.
Keywords: Bud bank; Photosynthetic pathway; Bud morphology and development; Plant architecture; Tiller recruitment; Vegetative reproduction; Biology, Botany (0309); Biology, Ecology (0329)